“It Used To Be Easy: In the Winter It Was Cold, in the Summer It Was Hot.” Emerging Socioecological Issues in the Quebec Community-Based Homelessness Sector - Roy, Mélissa; Larocque, Emmanuelle; Parent-Poisson, Nikolas; Lachapelle, Madeleine; MacDonald, Sue-Ann; Kidd, Sean (International Journal on Homelessness)

(untitled) (Western Libraries, University of Western Ontario, 2026)
People experiencing homelessness are disproportionately affected by climate-related socioecological challenges. While the impact of climate change on this population is increasingly studied, its collateral effects on community-based organization offering services to people experiencing homelessness are little explored internationally and undocumented in Quebec, Canada. Existing literature shows that such community-based services remain overall under-resourced and poorly-adapted, thus highlighting the need to study organizational realities. This collaborative study explored new climate realities’ effects on Quebec community-based organizations in the homelessness sector. We conducted three focus groups bringing together a total of 17 social services professionals from 7 administrative regions of Quebec. Professionals’ testimonies first show the broader issues that amplify the effects of socioecological problems on people experiencing homelessness, including stigma and social exclusion, political (in)action and organizational obstacles. In particular, results show that the climate crisis is filtered through a housing crisis, which together create new forms of climate vulnerability and new forms of housing precarity. Secondly, participants’ experiences testify to the complexities of climate unpredictability. This unpredictability highlights current gaps within the regional organization of services in the homelessness sector, which often open temporary environmental respite services based on anticipated seasonal climate patterns. This study highlights the pertinence of a “climate shelter” model, although this appears as the minimum required, with adequate housing being a first line of defense against new climate realities. Policy changes are proposed to enable a simultaneous response to both the climate and housing crises, guided by a socioecological justice perspective.